Modern library technologies for data storage, retrieval, and use - Wei, Chia-Hung, 1973-; IGI eBooks; IGI Global (Hershey, Pa. : IGI Global (701 E. Chocolate Avenue, Hershey, Pennsylvania, 17033, USA), 2013)
"This book highlights new features of digital library technology in order to educate the database community in the efforts to understand the applications of data acquisition, retrieval and storage"--Provided by publisher.
A unified algorithm for identification of various tabular structures from document images / Sekhar Mandal ... [et al.] -- efficient word segmentation and baseline localization in handwritten documents using isothetic covers / Mousumi Dutt ... [et al.] -- Hierarchical correlation of multi-scale spatial pyramid for similar mammogram retrieval / Jinn-Ming Chang ... [et al.] -- Mammogram retrieval: image selection strategy of relevance feedback for locating similar lesions / Chee-Chiang Chen ... [et al.] -- Traffic-signs recognition system based on FCM and content-based image retrieval / Yue Li, Wei Wang -- virtual magnifier-based image resolution enhancement / Lung-Chun Chang ... [et al.] -- A survey of digital forensic techniques for digital libraries / Yue Li -- Digital image authentication: a review / Yue Li, Chia-Hung Wei -- Decomposed PRNU library for forensics on photos / Yue Li -- Analysis the typhoon eyes of Megi from MTSAT satellite cloud images with 3-D profile reconstruction / Yueh-Jyun Lee ... [et al.] -- Agent negotiation in water policy planning / Menq-Wen Lin, Chia-Hung Wei, Pei-Cheng Cheng -- An affinity based complex artificial immune system / Wei Wang ... [et al.] -- Attitudes of librarians in selected Nigerian universities towards digital libraries in e-learning / Edwin I. Achugbue, Sylvester O. Anie -- Role of public libraries in bridging the digital divide / Owajeme Justice Ofua, Ogochukwu Thaddaeus Emiri -- Perceptions and attitude of students in relation to vandalism in university libraries in South-South zone of Nigeria / Owajeme Justice Ofua, Ogochukwu Thaddaeus Emiri -- ICT readiness of higher institution libraries in Nigeria / Pereware A. Tiemo, Nelson Edewor -- A presentation-preserved compositional approach for integrating heterogeneous systems: using e-learning as an example / Fang-Chuan Ou Yang -- Technostress: effects and measures among librarians in university libraries in Nigeria / Owajeme Justice Ofua, Tiemo Aghwotu Pereware -- Predicting users' acceptance of e-library from the perspective of technology acceptance model / Adeyinka Tella -- Analysis of success factors of introducing SAP system for ERP implementation in small and midsize enterprises in Taiwan / Hsin-Ju Wei, Chia-Liang Wei.
Includes bibliographical references.
Also available in print.
Mode of access: World Wide Web.
Description based on title screen (IGI Global, viewed January 17, 2013).
Keywords: Digital libraries; Information storage and retrieval systems; Multimedia systems; Architecture of digital library systems; Content and knowledge management; Data mining and extraction; Digital library applications; Human-computer interface design; Information visualization; Multimedia system integration; Electronic books